Teologi Pluralitas Multikultural (Perspektif Qurani) - Yusuf HM, Moh. (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2008)
The writing discusses the theology of multicultural pluralism. Theology is a scientific knowledge that discusses about God and Its relation to universe. It cannot be denied that the era of globalization creates the unity of civilization as the concequnce of informative communication development. Therefore, Islamic society have to maintain their identity and realize the existence of religious pluralism multiculturalism and egalitarianism. The term of